A high-gain edfa design using double-pass amplification with a double-pass filter - Bouzid, Belloui; Mohd. Ali, Borhanuddin; Abdullah, Mohamad Khazani (Institute of Electrical and Electronics Engineers (IEEE), 2003)
An erbium-doped fiber (EDF) amplifier configured in a double-pass amplification scheme together with a midway bandpass filter is presented to provide a gain as high as 37.5 dB with a noise figure of less than 6 dB. The system provides a gain improvement of as much as 9.5 dB from the double-pass system without filter. The system also can easily be upgraded to support dense wavelength-division-multiplexing (DWDM) transmissions by using a multiwavelength filter. Using a pair of four-channel DWDM multiplexer and demultiplexer, a gain of 39.53 dB for each of the channels was achieved. At the bit-error rate of 109, the proposed design supports the input level as low as -43 dBm with a gain of 37 dB. This is all achieved with the EDF length of 7 m and pump power of 90 mW.